STRESS AMONG LADY HEALTH WORKERS OF DISTRICT JACOBABAD - Muhammad Ibrahim Ansari; Chaudhry Muhammad Amjad; Khadim Hussain Maaari et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: AIM OF THE STUDY: To improve the working environment of the Lady Health Workers in Sindh. OBJECTIVES: To assess stress among the Lady Health Workers and to ﬁnd out the association in between stress and demographical variables. STUDY DESIGN: Quantitative Cross sectional study was done during the Nov; 2016 to March 2017, in Jacobabad District (Garhi Khairo, Thul and Jacobabad Taluka) among the Lady Health Workers working or attached with MCH centers. Simple random sampling technique were used and sample size calculated on prevalence rate, N=78. SRQ-20 (WHO inventory) questionnaire were used to collect data. SPSS 21.0 were used to analyses data and frequency tables and logistic regression were analyzed. RESULT: Response rate was 96%. The mean age of the LHWs was calculated age was 35.59+7.995 years, monthly income mean was 20500+438 and mean of job experience were 4.87+3.599 years. Marital status only found signiﬁcant p-value 0.04. CONCLUSION: Nature of Job of Lady Health Worker is mentally stressful which is altering the regular rotation of the human as well productivity of work.